E-Business and telecommunications : 13th International Joint Conference, ICETE 2016, Lisbon, Portugal, July 26-28, 2016, Revised selected papers /: 13th International Joint Conference, ICETE 2016, Lisbon, Portugal, July 26-28, 2016, Revised selected papers. (2017) - Unknown
No abstract available